Layer-specific serotonergic induction of long-term depression in the prefrontal cortex of rats - Shin, Dongchul (Korean J Physiol Pharmacol, 2020)
Layer 2/3 pyramidal neurons (L2/3 PyNs) of the cortex extend their basal dendrites near the soma and as apical dendritic tufts in layer 1, which mainly receive feedforward and feedback inputs, respectively. It is suggested that neuromodulators such as serotonin and acetylcholine may regulate the information flow between brain structures depending on the brain state. However, little is known about the dendritic compartment-specific induction of synaptic transmission in single PyNs. Here, we studied layer-specific serotonergic and cholinergic induction of long-term synaptic plasticity in L2/3 PyNs of the agranular insular cortex, a lateral component of the orbitofrontal cortex. Using FM1-43 dye unloading, we verified that local electrical stimulation to layers 1 (L1) and 3 (L3) activated axon terminals mostly located in L1 and perisomatic area (L2/3). Independent and AMPA receptor-mediated excitatory postsynaptic potential was evoked by local electrical stimulation of either L1 or L3. Application of serotonin (5-HT, 10 μM) induced activity-dependent long-term depression (LTD) in L2/3 but not in L1 inputs. LTD induced by 5-HT was blocked by the 5-HT(2) receptor antagonist ketanserin, an NMDA receptor antagonist and by intracellular Ca(2+) chelation. The 5-HT(2) receptor agonist α-me-5-HT mimicked the LTD induced by 5-HT. However, the application of carbachol induced muscarinic receptor-dependent LTD in both inputs. The differential layer-specific induction of LTD by neuromodulators might play an important role in information processing mechanism of the prefrontal cortex.